Endogenous Inequality in Integrated Labor Markets with Two-Sided Search - Mailath, George J; Samuelson, Larry; Shaked, Avner (American Economic Review, 2000)
We consider a market with “red” and “green” workers, where labels are payoff irrelevant. Workers may acquire skills. Skilled workers search for vacancies, while firms search for workers. A unique symmetric equilibrium exists in which color is irrelevant. There are also asymmetric equilibria in which firms search only for green workers, more green than red workers acquire skills, skilled green workers receive higher wages, and the unemployment rate is higher among skilled red workers. Discrimination between ex ante identical individuals arises in equilibrium, and yet firms have perfect information about their workers, and strictly prefer to hire minority workers. (JEL C70, D40, J30)